Ficopomatus enigmaticus larval development assay: An application for toxicity assessment of marine sediments. (February 2019) - Oliva, M.; Manzini, C.; Bontà Pittaluga, G.; Kozinkova, L.; De Marchi, L.; Freitas, R.; Fabi, G.; Pretti, C.
Abstract: Ficopomatus enigmaticus is a serpulid polychaete, reef-forming, dioecious gamete spawner throughout different seasons and in different salinity conditions. Due to these characteristics, its candidacy as a model organism to monitor both marine and brackish matrices was assessed. Marine sediments collected in a polluted area near the port of Ancona (Italy) were used as case study. Besides the chemical characterization of sediments, the larval development of F. enigmaticus was adopted as an assay for ecotoxicological assessment of sediments in addition to a regulatory bioassay battery with different organisms and endpoints. The quality of sediments was classified according to the Italian Ministerial Decree for sediment management (Ministerial Decree 173, 2016) by using the SEDI-QUAL-SOFT® (ver. 109.0) software developed by the Italian Environmental Protection Agency (ISPRA). The F. enigmaticus larval development assay showed a quite similar sensitivity to C. gigas larval development assays, indicating its potential use in a regulatory battery of bioassays. Highlights: F. enigmaticus larval development was adopted for ecotoxicological assessment of marine sediments within a test battery A Weight of Evidence-based approach was used as indicated by the Italian Ministerial Decree for sediment management Larval development assay with F. enigmaticus instead of C. gigas was investigated, showing a comparable sensitivity